Modular Tumor Resection Prosthesis in Osteosarcoma Treatment - Çirakli, A.; Sezgin, H.; Göçer, H.; Dabak, N. (Derman Medical Publishing secretary@jcam.com.tr, 2016)
Aim: The aim of the study is to evaluate the cases who underwent tumor resection prosthesis due to osteosarcoma. Material and Method: 14 cases who underwent tumor resection prosthesis due to osteosarcoma in our clinic between 2000 and 2012 and who had sufficient follow-ups were evaluated. The cases were examined in terms of gender, age, direction, tumor location, follow-up time, success of the treatment, complication, recurrence, and survival. The data obtained were transferred to the SPSS 15.0 program and analyzed. Normality distributions of the data were analyzed with the Shapiro-Wilk test. Results: 8 of the 14 cases were male, 6 were female, and the average age of the cases was 21.9±7.02. Osteosarcoma was in the distal femur in 9 (64.3%) of the patients, in the proximal tibia in 5 (35.7%) of the patients, in the right lower extremity in 5 of the patients, and in the left lower extremity in 9 of the patients. Average follow-up time was 33 months (3-144 months range). Average MSTS score was found as 81.9 (53-96 range), perfect results were taken in 11 (78.6%) patients while insufficient results were taken in 3 (21.4%) patients. As for complications, aseptic softening was observed in 3 cases, peroneal nerve paralysis was observed in 2 cases, skin necrosis was observed in 2 cases, periprostatic fracture was observed in 2 cases, prosthesis infection was observed in 1 case, and local recurrence was observed in 1 case. Except for the two cases with peroneal nerve paralysis, cases with complications recovered without any problems. The patient who developed local recurrence was lost due to lung metastasis. Discussion: Treatment of osteosarcoma through tumor resection prosthesis raises question marks due to possible complications that can affect the survival of the prosthesis in the long term. However, this treatment method is favorable in terms of stability, early load efficiency, and causing less anxiety than osteosynthesis; it is also psychologically more pleasing than amputation. © 2018, Derman Medical Publishing. All rights reserved.
Osteosarkom Tedavisinde Modüler Tümör Rezeksiyon Protezi
Keywords: Osteosarcoma; Result; Surgical Treatment; Tumor Resection Prosthesis